2020
DOI: 10.3390/children7090145
|View full text |Cite
|
Sign up to set email alerts
|

Parental Attitudes toward Artificial Intelligence-Driven Precision Medicine Technologies in Pediatric Healthcare

Abstract: Precision medicine relies upon artificial intelligence (AI)-driven technologies that raise ethical and practical concerns. In this study, we developed and validated a measure of parental openness and concerns with AI-driven technologies in their child’s healthcare. In this cross-sectional survey, we enrolled parents of children <18 years in 2 rounds for exploratory (n = 418) and confirmatory (n = 386) factor analysis. We developed a 12-item measure of parental openness to AI-driven technologies, and a 33-it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 54 publications
2
24
0
Order By: Relevance
“… 23 The majority (>70%) of parents of paediatric patients (n=804) reported openness to AI-driven tools if accuracy was proven, privacy and shared decision-making were protected and care using AI was convenient, of low cost, and not in any way dehumanised. 24 Among 48 US dermatology patients, most (60%) anticipated earlier diagnosis and better care access, while 94% saw the main function of AI as offering second opinions to physicians, and perceived AI as having both strengths (69% believed AI to be very accurate most of the time) and weaknesses (85% expected rare but serious misdiagnoses). 25 A small study found 18 patients with meningioma wanted assurance that use of AI to allocate treatment was fair and equitable, that AI-mediated mistakes would be disclosed and reparations to patients forthcoming and that patient consent was obtained for any sharing of health data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 23 The majority (>70%) of parents of paediatric patients (n=804) reported openness to AI-driven tools if accuracy was proven, privacy and shared decision-making were protected and care using AI was convenient, of low cost, and not in any way dehumanised. 24 Among 48 US dermatology patients, most (60%) anticipated earlier diagnosis and better care access, while 94% saw the main function of AI as offering second opinions to physicians, and perceived AI as having both strengths (69% believed AI to be very accurate most of the time) and weaknesses (85% expected rare but serious misdiagnoses). 25 A small study found 18 patients with meningioma wanted assurance that use of AI to allocate treatment was fair and equitable, that AI-mediated mistakes would be disclosed and reparations to patients forthcoming and that patient consent was obtained for any sharing of health data.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 27 articles were included of which most (16, 59%) targeted clinicians, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] 8 (30%) focused on consumers (including patients), [19][20][21][22][23][24][25][26] 1 (4%) on health executives 27 and 2 (7%) on industry stakeholders comprising AI vendors, researchers and regulators. 28 29 Detailed study descriptions are provided in the online supplemental appendix and summary results are listed in table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While patients generally had positive attitudes and trust in the technical aspects of AI, they expressed concern about the potential impact on the relationship with their clinicians. A literature review suggested that unfortunately patient attitudes towards AI are not usually included in clinical trials of healthcare AI applications (Scott et al, 2021), and some studies found that fear of dehumanisation of the relationship between patients and their clinicians was a significant concern (Esmaeilzadeh, 2020;Sisk et al, 2020). Such concerns echo findings from research about patient perceptions on their care, e.g., in the management of deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…Highquality reviews of AI in healthcare have addressed its use, value, and trustworthiness 3−6 . In children's healthcare, parents ask for openness during AI development, and ask that technical experts consider shared decision making, the human element of care and social justice as part of the development process 7 . However, whilst views of Children and Young People (CYP) can shape healthcare provision 8−11 , few policy recommendations reflect their views and beliefs 12−14 .…”
Section: Introductionmentioning
confidence: 99%